An Emerging Concept- Integrating Traditional Leadership and Virtual Leadership with special reference to Indian IT Industry - Sahay, Kasturi (International Journal of Information Studies, 2025)
The term leadership has been probably the most talked about subject. Decades of academic analysis have given us more than 350 definitions of Leadership (Bennis Warren, Harper and Row, 2005). Literally thousands of empirical interpretations of leaders have been conducted in the last 75 years alone but no clear and unequivocal understanding exists as to what distinguishes leaders from non-leaders. The time has come to not to talk of leadership in abstract terms but in concrete and measurable terms. Leadership has to be demystified, brought down from its lofty pedestrian, dissected and finally understood by the common man. Now as they say war is too important to be left to the Generals, likewise, leadership in an organization is too important a subject to be left behind to intuition, chance, whims and fancies of an individual. This is because leadership provided today has implication in the long term. Working and leading virtually have become a growing concern and hence a growing area of focus in the last few years, generated by an increased care for the environment, a concern for a better life quality, the need to cut costs and/or the desire to welcome Generation Y (people born in the ‘80s who have grown up with all virtual media) into the corporate world. However for most managers and leaders in organisations, working and leading virtually has remained an area of frustration, at best a ‘second-class’ way of working, something that you do when you have no other choice.